Trends in patient perceptions of care toward rural and urban hospitals in the United States: 2014‐2019 - Li, Zhong; Ho, Vivian; Merrell, Melinda A.; Hung, Peiyin (The Journal of rural health, 2024)
Purpose Understanding rural‐urban disparities in patient satisfaction is critical to identify gaps for improvement in patient‐centered care and tailor interventions to specific patient needs, especially those in the Frontier and Remote areas (FAR). This study aimed to examine disparities in patient perceptions of care between urban, rural non‐FAR, and FAR hospitals between 2014 and 2019. Methods This is a retrospective longitudinal study using 2014‐2019 Hospital Consumer Assessment of Healthcare Providers and Systems data linked to American Hospital Annual Survey data (3,524 hospitals in 2014 and 3,440 hospitals in 2019). Multivariable linear regression models were used to identify differential trends in patient perceptions of care by hospital rurality over 2014‐2019, adjusting hospital‐ and county‐level characteristics. Findings In 2014, patients at rural non‐FAR and FAR hospitals had lower percentages of willingness to definitely recommend these hospitals than urban hospitals (average percentage difference, 95% CI: −4.0% [−4.5%, −3.5%]; −2.0% [−2.8%, −1.2%]); yet, over the study period, rural hospitals experienced steeper increases in patient willingness to recommend (0.2% [0.07%, 0.4%]; 0.4% [0.08%, 0.7%]). FAR hospitals also showed improvements in patient experience in a clean environment, communication with nurses, communication about medicines, and responsiveness of staff. Communication with doctors showed slight decreases across hospital locations. Conclusions Patient perceptions of care were generally improved in all US hospitals from 2014 to 2019, except communications with doctors. These findings highlight the potential for enhancing patient satisfaction and experience in urban hospitals and suggest the need to improve patient willingness to recommend in rural FAR hospitals.